HUBUNGAN TINGKAT STRES DAN KEPRIBADIAN NEUROTICISM DENGAN PERILAKU EMOTIONAL EATING PADA MAHASISWA GIZI STIKES MITRA KELUARGA - Miosan Tasadeva Azalea; Noerfitri Noerfitri (Journal of Nutrition College, 2023)
ABSTRACTBackground: Students are one of the age groups that experience a lot of stress. Most of the stress experienced by students is caused by intrapersonal, interpersonal, academic activities, and environmental problems. Stress can affect eating behavior, someone who is experiencing stress tends not to eat or otherwise will overeat which has an impact on changes in nutritional status. Eating behavior is not only caused by hunger, but there are also other factors that influence it. Several factors that can influence eating behavior are mood, taste, and personality.Objectives: Analyze the relationship between stress levels and neuroticism personality with emotional eating behavior in STIKes Mitra Keluarga nutrition students.Methods: This research is quantitative research with a cross sectional design. The number of samples is 117 students of the S1 Nutrition STIKes Mitra Keluarga study program who were selected using the Simple Random Sampling technique. Data were collected using the Perceived Stress Scale (PSS), Big Five Inventory (BFI), and Dutch Eating Behavior Questionnaire (DEBQ). Data were analyzed using Chi-Square test.Results: Most of the respondents experienced a high level of stress (70.1%), had a moderate category of neuroticism personality (63.2%), and experienced a high category of emotional eating (52.1%). The significant relationship between variables is proven by the results of bivariate analysis which shows the p-value of each research variable, namely stress level (0.012) and neuroticism personality (0.016).Conclusion: There is a significant relationship between stress levels and neuroticism personality with emotional eating behavior in STIKes Mitra Keluarga nutrition students.Keywords: Emotional eating; Neuroticism personality; stress level. ABSTRAK Latar belakang: Mahasiswa merupakan salah satu kelompok umur yang banyak mengalami stres. Sebagian besar stres yang dialami oleh mahasiswa disebabkan dari masalah intrapersonal, interpersonal, kegiatan akademik, dan lingkungan. Stres dapat mempengaruhi perilaku makan, seseorang yang sedang mengalami stres cenderung tidak selera makan atau sebaliknya akan makan berlebihan yang berdampak pada adanya perubahan status gizi. Perilaku makan tidak hanya disebabkan oleh rasa lapar, tetapi juga terdapat faktor lain yang mempengaruhinya. Beberapa faktor yang dapat mempengaruhi perilaku makan adalah suasana hati, selera, dan kepribadian. Tujuan: Menganalisis hubungan antara tingkat stress dan kepribadian neuroticism dengan perilaku emotional eating pada mahasiswa gizi STIKes Mitra Keluarga.Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain cross sectional. Jumlah sampel sebanyak 117 mahasiswa program studi S1 Gizi STIKes Mitra Keluarga yang dipilih dengan teknik Simple Random Sampling. Data dikumpulkan dengan menggunakan kuesioner Perceived Stress Scale (PSS), Big Five Inventory (BFI), dan Dutch Eating Behaviour Questionnaire (DEBQ). Data dianalisis menggunakan uji Chi-Square.Hasil: Sebagian besar responden mengalami stress tingkat berat (70,1%), memiliki kepribadian neuroticism kategori sedang (63,2%), dan mengalami emotional eating kategori tinggi (52,1%). Hubungan yang signifikan antara variabel dibuktikan dengan hasil analisis bivariat yang menunjukkan nilai p-value pada masing-masing variabel penelitian yaitu tingkat stress (0,012) dan kepribadian neuroticism (0,016).Simpulan: Adanya hubungan yang signfikan antara tingkat stress dan kepribadian neuroticism dengan perilaku emotional eating pada mahasiswa gizi STIKes Mitra Keluarga.Kata Kunci: Emotional eating; Kepribadian neuroticism; Tingkat stres